2004
DOI: 10.1111/j.1365-2486.2004.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the total arrival distribution of migratory birds

Abstract: This paper reports on the total distribution of spring migration timing of willow warbler, chiffchaff and pied flycatcher at locations in the UK, Germany, Russia and Finland. This is the first time that high-quality data based on known-effort monitoring has been examined on a continental scale. First arrival dates, commonly reported in the literature, were positively correlated with mean arrival dates although they would not make good predictors of the latter. At all locations, at least one aspect of the arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 17 publications
11
150
3
1
Order By: Relevance
“…In keeping with recent studies of migration phenology (e.g. Vähätalo et al 2004;Sparks et al 2005;Tøttrup et al 2006), we defined change as the slope of a linear regression of an annual value of Julian day against year. This provides an estimate of the average annual change in migration date, measured in days, in which negative slopes indicate earlier migration, and positive slopes later migration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with recent studies of migration phenology (e.g. Vähätalo et al 2004;Sparks et al 2005;Tøttrup et al 2006), we defined change as the slope of a linear regression of an annual value of Julian day against year. This provides an estimate of the average annual change in migration date, measured in days, in which negative slopes indicate earlier migration, and positive slopes later migration.…”
Section: Methodsmentioning
confidence: 99%
“…We used this percentage rather than the day of the first individual of the season (e.g. Tryjanowski et al 2002) because it is much less susceptible to stochastic and sampling effects (see also Sparks et al 2005;Tøttrup et al 2006 for discussion). Owing to the predominance of protandry, this segment is likely to comprise largely males.…”
Section: Methodsmentioning
confidence: 99%
“…This pattern may arise because most individuals respond rapidly and similarly to the relevant environmental cues, while a smaller number experience problems in development or migration that delay phenology to varying extents (Rathcke & Lacey 1985;Danks 2006). Intriguingly, skewness often increases in warm years, with populations developing a longer tail at the end of the season (Roy & Sparks 2000;Sparks et al 2005;. Skewness also determines the extent to which an individual's timing of activity covaries with population density.…”
Section: Characterizing Phenologies At the Population Levelmentioning
confidence: 99%
“…Timing of germination and flowering in plant populations is often positively skewed (Rabinowitz et al 1981;Rathcke & Lacey 1985;Brown & Mayer 1988), as are timing of emergence in insects (Danks 2006) and arrival and laying dates in migratory birds (Sparks et al 2005;Laaksonen et al 2006). This pattern may arise because most individuals respond rapidly and similarly to the relevant environmental cues, while a smaller number experience problems in development or migration that delay phenology to varying extents (Rathcke & Lacey 1985;Danks 2006).…”
Section: Characterizing Phenologies At the Population Levelmentioning
confidence: 99%
“…It is well known that the transmission cycle involves birds as the principal hosts (and mosquitoes, largely bird-feeding species, as the primary vectors) [23]. In recent years, it has been observed that several bird species have been migrating to their breeding grounds earlier as a result of an early rise of the mean spring temperatures, which is one of the effects of global warming [46][47][48][49][50]. This phenomenon might influence the appearance and timing of the disease in locations near or along migration routes.…”
Section: (A) Temperaturementioning
confidence: 99%